Fast water transport through biomimetic reverse osmosis membranes embedded with peptide-attached (pR)-pillar[5]arenes water channels - Lim, Yu Jie (2022)
This study examined the feasibility and performance of a nanochannel-based biomimetic membrane (NBM) for brackish reverse osmosis (RO) desalination. Two types of peptide-attached synthetic nanochannels, (pR)-pillar[5]arenes (pRPH) and (pS)-pillar[5]arenes (pSPH), were incorporated into liposomes. pSPH is a diastereomer of pRPH and was used as a negative control (i.e. mutant) to pRPH in this work. The nanochannel-containing liposomes (e.g. pRPH-liposomes) were then immobilized into the active layer of the RO membranes via in situ interfacial polymerization on the top of a polysulfone support membrane to form NBM-pRPH membranes. To maximize the potential and benefits of the NBM-pRPH membrane, the physical characteristics of the polyamide layer was further tuned using some additives and the eventual membrane was named as NBM-pRPH-A. The NBM-pRPH-A membrane exhibited a water permeability of 6.09 L m−2 h−1 bar−1 and 98.2% NaCl rejection under a 15.5 bar applied pressure using 2000 mg L−1 as feed solution. The 62% flux increment with respect to the pristine control is postulated to arise from a thinner, less cross-linked (more free volume) and more hydrophilic active layer as well as the possible supplementary transport pathways of the pRPH-liposomes. The performance of the NBMs under differential feed pressures and temperatures further exemplifies the water permeation property of the pRPH nanochannels. Accordingly, the NBM-pRPH-A gave a water permeability higher than commercial RO membranes tested in this work (DuPont BW30 and Hydranautics ESPA2) as well as other RO membranes reported in the literature. This study provides a tangible foundation for the development of NBMs for brackish RO desalination.